Discourse on the Middle Class in Post-Communist Context - Gečienė, Ingrida (Sociologija. Mintis ir veiksmas, 2005)
The focus of this article is to reveal some ambiguities existing in discourse on middle class, particularly on causal relationship between the middle class and democracy, and to show some risk in applying such Western theoretical framework in post-Communist context. Therefore, the essential purpose has been to ask: what explanatory power does the term ‘middle class’ have in the analysis of post-Communist societies? Does the term really help us to understand the actual situation within the rapidly changing societies of the region, or does it serve only as a powerful metaphor of their ‘backwardness’ in comparison with Western ones? The practice of transferring Western theoretical tools to other social contexts is hardly new. We need only think of the transfer of United States modernisation theory to explain the ‘backwardness’ of Latin America. The theory and its constituent elements did not fit these societies precisely because the theory succeeded only in showing them up as backward in terms of the modernisation process. Similarly, if to use the concept of the middle class as purely descriptive tool for analysing post-Communist social reality, then it quickly becomes apparent that such phenomenon as the middle class hardly exist, at least not in the form it takes in Western countries. However, such implication says nothing about particular social realities or about the degree of democratic development in post-Communist countries. The enormous emphasis placed on the middle class in post-Communist intellectual discourse makes one aware that this concept is used not so much as a theoretical tool in explaining social reality than as an ‘ideological artefact’. Therefore, we can speak about signs of an ideological manipulation of theoretical assumptions, employing otherwise quite artificial models for the construction of compliant social structures, or at least presenting a simulacrum of them from above. Besides, the common practice of transferring Western models to the East points towards the dominance of Western political programmes in setting research agendas and in attracting sponsorship for academic work. Such negative effects simultaneously lead us to look critically at any direct application of Western concepts to the post-Communist world and inspire us to look for more adequate approaches and theories with which to explain the social reality of the region.
Keywords: middle-class; post-Communist society; convergence; democracy